Oscar Tuazon : I can't see - Boutoux, Thomas; Letué, Pierre-François; Perret, Dorothée; Centre international d'art et du paysage de l'île de Vassivière; Kunsthalle Bern.; Parc Saint Léger--Centre d'art contemporain (Paris : Do.Pe. Press, 2010)
"I think with my hands, I think of my hand as a man. Sort of a man, short of a man. A man and a half. Half a man, half a hand. I give myself a hand. I can't remember ever wanting to be anything. If I ever wanted anything. If I ever wanted anything I got it, but I never wanted it. I use my body for something, I use it to make something, I make something with my body, whatever that is. I make something and I pay for it and I get paid for it. I get laid for it. I get something out of it, I put something into it and I get something out of it, I get out of it. I sweat it out. I stick it out, I spit it out, I put something into my body then I spit it out. I want to put something inside my body and carry something in it. I want to get inside my body and get carried in it, I'd like to get buried in it, put my head in it and get in it, I'm not scared of it. I'm walking as I write this. Working. That's why I'm here: I'm here to work. I came here to work. They needed another body on it and so I got on it. I walked up to get some work. I walk to work. I came up here to get some work. I climbed up a sheet and stood on it. That's what I'm paid to do so I do it. Whatever else it is I do is my business, as long as I do the job, and I do do the job. Walk out till the road ends, then walk till I can't see it, then walk till I can't talk, then stop. I can't talk. I'm the one who has to do that, I'm the one to do it so I do it. I don't have a say in it, they pay for it and I stay at it. I'm the one paid to do it, I'm the one who stayed to do it, I stayed and did it, they paid and quit it. Someone else could do it if they're paid to do it, but who else would do it? I knew what I had to do so I do it, just stay true to it and try to get through it."--P. [4] of cover.
Catalog of the exhibition "Bend It Till It Breaks", held at Centre international d'art et du paysage de l'Ile de Vassivière, Beaumont-du-Lac, Nov. 15, 2009-Feb. 14, 2010; "Oscar Tuazon" at Kunsthalle Bern, Feb. 13-Apr. 25, 2010; the exhibition with Elias Hansen, "It Was One of my Best Comes", at Parc Saint Leger, Centre d'art contemporain, Pougues, France, March 20-June 6, 2010.
boek
Keywords: Tuazon, Oscar